Analisis Manajemen Piutang Dalam Meminimalisisr Resiko Piutang Tak Tertagih Pada PT Multi Pilar Indah Jaya (Distributor PT Unilever Indonesia Tbk) Kota Gunungsitoli - Dian Nikita Zebua; Maria Magdalena Bate’e; Yakin. N. Telaumbanua (Universitas Sam Ratulangi, 2022)
Accounts receivables is one of the current assets owned by a company as a result of credit sales made by the company. However, the existence of receivables owned by a company will pose a risk of bad debt. At PT Multi Pilar Indah Jaya (Distributor PT Uniever Indonesia Tbk) Kota Gunungsitoli itself also has bad debts due to the inneffective control of receivables carried out by the management. The purpose of this study is to find out how to control accounts receivable in minimizing bad debts at PT Multi Pilar Indah Jaya (Distributor PT Unilever Indonesia Tbk) Kota Gunungsitoli. This study uses descriptive qualitative researh where the author analyzes the receivables data and provides a detailed description of the research results. The source of the data for this research is interviews and observations conducted at PT Multi Pilar Indah Jaya (Distributor PT Unilever Indonesia Tbk) Kota Gunungsitoli. Based on an analysis of receivables for the last three years (2019-2021) the percentage of bad debts has increased due to the impact of the Covid-19 pandemic, which has caused the receivables control system to be ineffective, therefore it is necessary to implement a government policy by not implementing Large-Scale Social Restrictions (PSBB). The results of the study obtained after the government did not implement large-scale social restrictions (PSBB) and carried out good management, namely bad debts decreased. Keywords : Accounts receivable management, Bad debts, Covid-19, Government